ЛИНГВОКУЛЬТУРОЛОГИЧЕСКИЕ ОСОБЕННОСТИ КОНЦЕПТА «MOTHERLAND/ЎАТАН» В РАЗНОСИСТЕМНЫХ ЯЗЫКАХ - Рзаева, Р.К. (SCIENCE and SOCIETY, 2019)
The article deals with the comparative-contrastive investigation of the concept «Motherland/Ўатан» in the literary works of the famous English and Karakalpak poets. The analysis of the concept «Motherland/Ўатан» shows that there are common similar and distinguishing features in expression of this concept in English and Karakalpak. The distinguishing peculiarities in verbal expression in the languages belonging to different systems can be explained by differences in the culture of different nationalities and countries.
Keywords: Cognitive Linguistics; concept; linguoculturology; comparative-contrastive investigation; national peculiarities; culture; ethnos; similarities and differences; traditions and customs